-3(2s-1)-3=-2(s+8)-2

Simple and best practice solution for -3(2s-1)-3=-2(s+8)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2s-1)-3=-2(s+8)-2 equation:


Simplifying
-3(2s + -1) + -3 = -2(s + 8) + -2

Reorder the terms:
-3(-1 + 2s) + -3 = -2(s + 8) + -2
(-1 * -3 + 2s * -3) + -3 = -2(s + 8) + -2
(3 + -6s) + -3 = -2(s + 8) + -2

Reorder the terms:
3 + -3 + -6s = -2(s + 8) + -2

Combine like terms: 3 + -3 = 0
0 + -6s = -2(s + 8) + -2
-6s = -2(s + 8) + -2

Reorder the terms:
-6s = -2(8 + s) + -2
-6s = (8 * -2 + s * -2) + -2
-6s = (-16 + -2s) + -2

Reorder the terms:
-6s = -16 + -2 + -2s

Combine like terms: -16 + -2 = -18
-6s = -18 + -2s

Solving
-6s = -18 + -2s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '2s' to each side of the equation.
-6s + 2s = -18 + -2s + 2s

Combine like terms: -6s + 2s = -4s
-4s = -18 + -2s + 2s

Combine like terms: -2s + 2s = 0
-4s = -18 + 0
-4s = -18

Divide each side by '-4'.
s = 4.5

Simplifying
s = 4.5

See similar equations:

| 5u(u-8)(u-3)=0 | | Z-3*10=10 | | I-19I= | | 6y+13=55 | | X+4+3=17 | | 25x-10-16X=3(3X-4)+2 | | 3y-5+y+33=8y+30-6y | | Y=0.493x-973.4 | | 58=11x+3 | | 13x+72=-7x-28 | | 11-3x+5=10 | | 6.4x+2.3x=-65.6 | | 5(x+5)+3=18 | | 17x+4=-21-8x | | 4(2x+1)-3x=14 | | 12x^4y^3-20x^2y=0 | | a^3-125= | | 8w+3=5w+7+4w | | 6.4x-2.3x=65.6 | | 8-3(5-x)=14 | | 6x+11x=85 | | 4x-9x+5=10 | | 2x^2y+4xy-24y= | | 6y+42=4y | | 7(3x+4)=5(5x-4) | | 12x+4y=20(x) | | 7g+h=-2 | | -6x+5=77 | | 4(3y+6m)+-6y+14m= | | 6+2x=4(x+3) | | 4n+2=-4n+-2 | | 3x^2-28x-20=0 |

Equations solver categories